Strength Analysis of a 3-Joint Robogripper Robot Manipulator System Prototype for Lifting 50 Gram Goods - Gunawan Hidayat; Hendro Purwono; Rasma; Bambang Setiawan; Sri Anastasia Yudistirani (Jurnal Teknologi, 2026)
The design of a 3-joint robogripper system manipulator hand robot for a maximum lifting capacity of 50 grams has a lifting and transport capacity for workpieces with a maximum weight of 50 grams using a servo motor mounted on a robot frame made of acrylic material and can rotate 180 ̊ with a maximum reach of 500 mm. process that still heavily relies on human labor in the manufacturing industry is lifting and transporting, particularly in the jewelry industry. This requires the operator's expertise to lift and transport the jewelry without leaving fingerprints on the surface and into the packaging.To meet the needs described above, a change in the work process is necessary. This change reduces the operator's skill requirement and can reduce human error, which can lead to product failure during quality control.Based on the shortcomings of the previous work process described, a lifting and transporting machine is needed that achieves maximum results without relying on operator skill and in shorter processing times. One machine that can be implemented to achieve the desired results is the robogripper robotic arm.The design of a 3-joint robogripper system manipulator hand robot for a maximum lifting capacity of 50 grams has a lifting and transport capacity for workpieces with a maximum weight of 50 grams using a servo motor mounted on a robot frame made of acrylic material and can rotate 180 ̊ with a maximum reach of 500 mm. and 250 mm from the center point of the robot. This hand robot aims to be a gold bar lifting tool with a maximum capacity of 50 grams so that it can reduce the number of rejects in the form of A fingerprints on the surface of goods caused by manual.